2020
DOI: 10.1182/bloodadvances.2019001299
|View full text |Cite
|
Sign up to set email alerts
|

Passively transferred IgG enhances humoral immunity to a red blood cell alloantigen in mice

Abstract: Antibodies are typically thought of as the endpoint of humoral immunity that occur as the result of an adaptive immune response. However, affinity-matured antibodies can be present at the initiation of a new immune response, most commonly because of passive administration as a medical therapy. The current paradigm is that immunoglobulin M (IgM), IgA, and IgE enhance subsequent humoral immunity. In contrast, IgG has a “dual effect” in which it enhances responses to soluble antigens but suppresses responses to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 32 publications
(36 reference statements)
9
42
0
Order By: Relevance
“…Why IgG2a and IgG2b enhanced in the current (and recent) reports ( 11 ) but suppressed in the report by Yu et al ( 29 ) is unclear. However, it is worth noting that each of the antibodies used by Yu et al ( 29 ) had different antigen binding domains, different affinities, and bound to different epitopes; as such, it is not possible to isolate IgG subclass as an independent variable.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Why IgG2a and IgG2b enhanced in the current (and recent) reports ( 11 ) but suppressed in the report by Yu et al ( 29 ) is unclear. However, it is worth noting that each of the antibodies used by Yu et al ( 29 ) had different antigen binding domains, different affinities, and bound to different epitopes; as such, it is not possible to isolate IgG subclass as an independent variable.…”
Section: Discussionmentioning
confidence: 61%
“…The observed ability of IgG2a and IgG2c to enhance alloimmunity to RBC alloantigens in mice is not particular to the K1 system or the PUMA1 antibody; we recently reported a similar effect using a different RBC alloantigen (HOD RBCs) and a distinct panel of switch variants from a monoclonal antibody recognizing a Duffy epitope on the HOD RBCs (PUMA6) (11). In this case, IgG2a, and IgG2c (but not IgG2b) enhanced IgM and IgG responses to HOD.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Recently, we have reported that pre-treatment of mice with an IgG2c specific for an RBC antigen can substantially enhance the humoral immune response upon transfusion of RBCs expressing that antigen (16,17). Herein, we tested antigen copy number as an independent variable with regards to how IgG2c affects immune response.…”
Section: Introductionmentioning
confidence: 99%